Pengaruh Orientasi Kewirausahaan Terhadap Kinerja Usaha Kecil dan Menengah ( Studi Kasus Usaha Makanan Ringan di Kota Pagar Alam ) - Ahmad Feriyansyah; Febriansyah Febriansyah (UNIVED Press, 2023)
This study aims to determine the effect of entrepreneurial orientation on the performance of Small and Medium Enterprises (Snack business study in Pagar Alam City). The type of research used is associative research, the number of samples used in this study is 10 respondents, the data analysis method used is simple linear regression analysis, t test, and coefficient of determination analysis. Analysis of the data obtained a coefficient of determination of 91.0%,This means that the entrepreneurial orientation variable has a large effect on the performance of the snack business in Pagar Alam. 9.0% is influenced by other variables not examined in this study. Then from the hypothesis test the entrepreneurial orientation has a significant effect on performance Small and Medium Enterprises which are proven from the results of the t test where the significance level is obtained below 0.05 or sig 0.000 <0.05 so that the hypothesis is accepted.